2017
DOI: 10.1002/ajcp.12207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Food Policy Councils Using Structural Equation Modeling

Abstract: At least 282 Food Policy Councils (FPCs) are currently working to improve access to healthy foods in their communities by connecting food system sectors, gathering community input, and advising food policy. Empirical research on FPCs is limited. This study empirically evaluates FPCs to better understand the relationships between Organizational Capacity, Social Capital, and Council Effectiveness by testing a FPC Framework adapted from Allen and colleagues (2012). Members of all FPCs in the U.S., Canada, and Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…We therefore consider FPC membership to be an FPC attribute that can affect who is included in public participation opportunities, which is consistent with other research into FPC effectiveness (e.g. (Calancie, Allen, et al, 2018)). Our results show great variety among some of the attributes of the 12 surveyed New England FPCs engaged in policy efforts, including geographic scale and organization type ( Table 1).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…We therefore consider FPC membership to be an FPC attribute that can affect who is included in public participation opportunities, which is consistent with other research into FPC effectiveness (e.g. (Calancie, Allen, et al, 2018)). Our results show great variety among some of the attributes of the 12 surveyed New England FPCs engaged in policy efforts, including geographic scale and organization type ( Table 1).…”
Section: Resultsmentioning
confidence: 59%
“…At least half of FPCs operating in the U.S. and Canada report that their membership includes individuals from the following groups: community, public health, anti-hunger/emergency food organizations, producers, colleges/universities, government staff, healthcare, labor, retail, social justice, and economic development (Bassarab et al, 2018). A second survey of these FPCs found that breadth of membership is an important determinant of FPC effectiveness (Calancie, Allen, et al, 2018).…”
Section: Research On Food Policy Councils and Inclusive Public Particmentioning
confidence: 99%
“…Calancie et al. () used structural equation modeling to examine associations between coalition leadership, climate, membership breadth, and structure with member perceptions of effectiveness. Nargiso et al.…”
Section: Resultsmentioning
confidence: 99%
“…They then used mixed model regression to examine capacity-related predictors and adolescent alcohol outcomes collected through middle and high school student surveys. Calancie et al (2018) used structural equation modeling to examine associations between coalition leadership, climate, membership breadth, and structure with member perceptions of effectiveness. Nargiso et al (2013) examined correlations between diversity, structure, task focus, cohesion, and number of policy changes in substance use prevention coalitions.…”
Section: Associations Between Coalition Characteristics and Coalitionmentioning
confidence: 99%
“…At the community level, findings highlight FM use is facilitated or constrained by some factors that are beyond the control of an individual that may be addressed through macro‐level change fostered by local food policy coalitions (Calancie et al., ). Our study offers evidence to support efforts to promote ease of access to FMs through strategic location, such as aligning FMs with public transportation or within settings where low‐income consumers reside and/or work.…”
Section: Discussionmentioning
confidence: 99%